Heating and destruction of biological tissue by high-inensity focused ultrasound - Andreeva, T.A.; Berkovich, A.E.; Bykov, N.Y.; Kozyrev, S.V.; Lukin, A.Ya. (Peter the Great St. Petersburg Polytechnic University, 2019)
Processes of heating and destruction of the breast fat tissue under the action of
focused high-intensity ultrasound generated by a 128-element transducer are considered. The
simulation of a thermal problem is carried out by anumerical solution of the heat transfer
equation. The acoustic pressure field in the tissue is calculated using the Rayleigh integral. A
system of dimensionless scaling parameters is proposed to describe the non-stationary process
of heat propagation. The influenceof the space localization of foci in a series of pulses on the
lesion size is analyzed. The results demonstrate the advantages of a tissue processing program
withspatially divergingfocal points of pulses, consisting in a more uniform heating of the
tissue and the formation of a continuous ablation area. The impact of the perfusion process on
the lesion size is considered.